Research of Flow Characteristics on Spilling Waves. (2015) - Xiangyu, Gao; Xiping, Dou; Gaozhengrong,; Lei, Ding; Yun, Pan
Abstract: This paper uses ADV to measure the characteristics of velocity field near breaking wave over a gentle slope (1/200) in a wave flume. The result indicates that: The phase difference of the maximum velocity of vertical direction and horizontal direction is about T/8. The maximum velocity in the horizontal direction is several times larger than that in the vertical direction. The velocity in the wave crest is larger than that in the wave trough. The smallest maximum velocity around breaking wave happens in the wave breaking point. At the breaking wave point and after wave breaking, the asymmetry is obvious.